Strategi Berkelanjutan untuk Transformasi Permukiman Kumuh di Kawasan Pesisir Tanjungmas Semarang - Prima Ariaoktafiani (Jurnal Ilmiah Membangun Desa dan Pertanian, 2024)
Tanjungmas, a coastal neighborhood in Semarang City, Indonesia, has experienced rapid urbanization due to its strategic location as a trade and maritime hub. This growth, however, has triggered the emergence of slum settlements characterized by overcrowding, poor infrastructure, and limited access to essential services, significantly reducing residents' quality of life. Addressing these challenges is essential to fostering sustainable urban development. This study aims to assess the existing conditions of slum settlements in Tanjungmas and propose actionable strategies to improve their quality. Adopting a qualitative approach, data collection involved field observations, interviews with local households, and secondary data analysis from government and urban planning reports. The study utilizes SWOT analysis to assess internal strengths and weaknesses and external opportunities and threats. Key findings reveal critical issues, including inadequate sanitation, poor drainage systems, lack of clean water access, and limited economic opportunities for residents. The research highlights the importance of strengthening community participation in urban development planning alongside increased government collaboration and investment in essential infrastructure. Proposed strategies include involving the community in planning, executing, maintaining urban infrastructure, and expanding sustainable economic initiatives through small businesses. Additionally, fostering public-private partnerships can provide funding and technical support for improving housing conditions. Transparent governance and the integration of local knowledge are vital for ensuring the sustainability of these efforts. This study offers valuable insights into the complexities of slum settlement dynamics in coastal areas and provides a roadmap for policymakers to address similar challenges. The strategies outlined aim to enhance living standards for residents of Tanjungmas while offering a replicable model for slum improvement in other urban coastal areas.